Effect of Guava Juice and Papaya Juice on Increasing the Hemoglobin Levels among Pregnant Women - Sri Yati; Rizky Amelia; Dhita Aulia Octaviani; Maya Erisna (International Journal of Nursing and Health Services (IJNHS), 2020)
Anemia is a significant public health problem with a prevalence of about 2 billion around the world.  Consuming the iron (Fe) tablets or foods containing iron were strategies for preventing iron deficiency. Vitamin C or ascorbic acid can increase iron absorption 4-fold, and an amount of 200 mg will increase iron absorption by at least 30%. Guava (Psidium Guajava) and papaya (Carica Papaya Linn) are examples of fruits that contain lots of ascorbic acids. The study aimed to investigate red guava juice and papaya juice on hemoglobin levels in pregnant women. This study applied the pre-experimental research with two groups, pre-test and post-test, without the control group. Thirty pregnant women were divided into two groups, such as group 1 received the Guava (n=15), and group 2 received the papaya (n=15). A paired T-test was used to test the mean value of pre-test and post-test within the group. An Independent t-test was done to determine the difference between groups. This study showed an increase in hemoglobin after two weeks of guava juice and papaya juice supplementation. However, the Independent t-test showed no significant difference between the two groups with a value of 0.617 (p >0.05). Both supplementations of 200 ml/day red guava juice and papaya juice with iron tablets for 14 weeks are equally effective in increasing hemoglobin levels in second and third-trimester pregnant women